Effect of Concept Mapping Instructional Strategy on Senior Secondary School Students’ Scoring Levels in Biology in Kwara State - Oyeyemi, Waheed Tunde; Olorundare, Adekunle Solomon; Bolaji, Hameed Olalekan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The study examined the effect of concept mapping instructional strategy on senior secondary school students’ scoring levels in biology in Kwara State. A quasi-experimental research design of pretest, posttest, and control group was used. The target population was 852 Secondary School Students (SSS II) from two selected public senior secondary schools in Ilorin, Kwara State. The sample consisted of 80 Senior Secondary School II Biology students purposively selected from two Public Secondary Schools in Ilorin, Kwara State, Nigeria. The adapted Biology Concept Map Instructional Strategy for Teaching Cell Division (BCMISTCD) and Scores from the Biology Performance Test (BPT) were used for data collection. The instruments were duly validated by experts. The reliability of the Biology Performance Test (BPT) instrument was .83. Frequency count, percentage, mean and standard deviation to answer the research questions (1-2). Analysis of Covariance (ANCOVA) and T-test were used to test the null hypotheses 1-2 at 0.05 level of significance. Results show that there is a significant difference in the scoring levels of Biology students when concept mapping instructional strategy is used to teach Cell Division (p.<0.05). The study also indicates that there is a significant difference in the male and female students scoring levels when concept mapping instructional strategy is used to teach Cell Division (p.<0.05). Based on the results, the study concludes that there is a significant difference in the post-test and post-posttest scoring levels of the students when concept mapping instructional strategy is used to teach them. The study also concludes that male students’ scoring level is higher than that of female students when concept mapping instructional strategy is used to teach Cell Division. The study recommends that Biology teachers should teach female students who have low-scoring levels in Biology by using concept concept-mapping instructional strategy. This would further improve the female students’ scoring levels in the Cell Division. The study recommends that Biology teachers should focus more on female students when concept mapping is used to teach Cell Division. Keywords: concept mapping, scoring levels, cell division, biology students, gender